Comparison of chromogenic and cysteine lactose electrolyte deficient agar for identification of uropathogens in Gujarat, India - Nisha Vadivelu; Rashmika D. Parmar; Hitesh Shingala; Krunal D. Mehta (African Journal of Laboratory Medicine)
Background: Urinary tract infections (UTIs) are prevalent bacterial infections, necessitating rapid and accurate diagnosis for timely treatment. Conventional culture techniques, such as cystine lactose electrolyte deficient (CLED) agar, can delay treatment and contribute to inappropriate antibiotic use. Not much is known about alternatives such as chromogenic UTI agar.